The Effectiveness of Cananga Aromatherapy with Warm Compress in Reducing Premenstrual Syndrome (PMS) Amongst Teenage Girls - Nur Meity Sulistia Ayu (Department of Nursing Universitas Jenderal Soedirman, 2019)
Abstract Premenstrual Syndrome (PMS) appears 7-10 days before the menstrual period and can cause an uncomfortable feeling and pain with mild to severe symptoms that eventually can disturb the activities and quality of life of teenage girls. Prolonged use of chemical medication can cause several side effects.  However, there is the option to use complementary therapy, such as Cananga aromatherapy with a warm compress, which is considered to be safer than chemical medication and has no side effects. The purpose of this research is to investigate the effectiveness of Cananga aromatherapy with a warm compress in reducing PMS in teenage girls. This research is a quasi experimental, pretest and posttest with control group design. Consecutive sampling was used to generate 68 respondents from teenage girls who were then divided into two groups  -  the intervention group that was given Cananga aromatherapy with a warm compress and the control group who did not receive the  intervention. The bivariate analysis in the experimental group after the intervention, using the Cochran test, showed that the Cananga aromatherapy with a warm compress is effective in reducing PMS amongst teenage girls (p=0,000 < ? = 0,05). Another analysis using the Kolmogorov-Smirnov test showed that there is a difference in the level of PMS between the experimental and the control group (p=0,002 < ? = 0,05). It is therefore recommended that Cananga aromatherapy with a warm compress be used as a complementary therapy to reduce PMS amongst teenage girls.   Key words: Premenstrual Syndrome; PMS, Cananga Aromatherapy; Warm Compress; Teenage Girls